KAJIAN HUKUM TERHADAP KEWENANGAN KEPALA DAERAH DALAM PENCABUTAN IZIN PERTAMBANGAN BATUBARA (Studi Di Wilayah Kabupaten Kutai Timur) - Evian Agus Saputra (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
Regent of East Kutai in 2007 issued a Mining Permit for General Survey (PU) being applied by the PT Sarita Prima Coal, so regent issued a decree East Kutai Regent Number: 597/02.188.45/HK/XI/2007 concerning Permit Renewal Authority Mining General Survey to PT. Sarita Prima Coal covering 25,000 hectares which is located in Muara District Ancalong East Kutai regency.After a year since the permits issued and carried out evaluation of the company's mining permit holders in the East Kutai regency, which is meant the company was PT.Sarita Prima Coal, including those considered to neglect the rights and obligations for mining and other efforts related to the environment and so forth based on findings of which have never paid Fund Appropriation Region, Pays Fixed Annual Fee and Guarantee all seriousness has never been paid to Local Government. From the results of studies of and evaluation of Spatial Control Team and the East Kutai regency, then based on the Decree on the second dictum h letter issued on the permit holder and the East Kutai District Regulation Number : 13 Year 2004 on Regional General Mining Permit Article 20 paragraph 1 letter c, then the Regents authority to revoke the permit issued Decree East Kutai Regent Number :  188.4.45/569/HK/XI/2008 concerning Revocation of DecreeEast Kutai Regent  Number : 597/02.188.45/HK/XI/2007 about Mining Permit Renewal Public Inquiry to PT. Sarita Prima Coal covering 25,000 hectares which is located in Muara District Ancalong East Kutai regency.License Revoked by the Regents and / or other authorized officials, because, in violation of applicable regulations as contained in the regulation of this area, and / or other legislation applicable in the field of mining and did not meet the obligations specified in the relevant Permit, Holder IUP who did not carry out mining activities without giving reasons that can be accountedfor.Revocation of this is the PT. Sarita Prima Coal who feel aggrieved to sue the local government in this case as a regent who issue permits. The law suit filed in Samarinda State Administrative Court. At the first level Court decision dated June 25, 2009, the Defendant is the regent of East Kutai won. Plaintiff PT. Sarita Prima Coal appealed to the Court of Level II in the State Administrative High Court of Jakarta which is precisely the verdict in favor of the plaintiff even / Comparative PT. Sarita Prima Coal. The process of both parties are parties of the Local Government to re-appeal to the Supreme Court until now the process is still ongoing.Implementation of the mining of the existing system in the East Kutai regency there are some weaknesses, namely the Environmental Control, Risk Assessment, Control Activities, Information and Communication, Monitoring, including the permit issued.